Characteristics of children readmitted with severe pneumonia in Kenyan hospitals - Diana Marangu-Boore; Paul Mwaniki; Lynda Isaaka; Teresiah Njoroge; Livingstone Mumelo; Dennis Kimego; Achieng Adem; Elizabeth Jowi; Angeline Ithondeka; Conrad Wanyama; Ambrose Agweyu (BMC, 2024)
Abstract Background Pneumonia is a leading cause of childhood morbidity and mortality. Hospital re-admission may signify missed opportunities for care or undiagnosed comorbidities. Methods We conducted a retrospective cohort study including children aged $$\ge$$ ≥ 2 months-14 years hospitalised with severe pneumonia between 2013 and 2021 in a network of 20 primary referral hospitals in Kenya. Severe pneumonia was defined using the 2013 World Health Organization criteria, and re-admission was based on clinical documentation from individual patient case notes. We estimated the prevalence of re-admission, described clinical management practices, and modelled risk factors for re-admission and inpatient mortality. Results Among 20,603 children diagnosed with severe pneumonia, 2,274 (11.0%, 95% CI 10.6-11.5) were readmitted. Re-admission was independently associated with age (12-59 months vs. 2-11 months: adjusted odds ratio (aOR) 1.70, 1.54-1.87; >5 years vs. 2-11 months: aOR 1.85, 1.55-2.22), malnutrition (weight-for-age-z-score (WAZ) <-3SD vs. WAZ> -2SD: aOR 2.05, 1.84-2.29); WAZ − 2 to -3 SD vs. WAZ> -2SD: aOR 1.37, 1.20-1.57), wheeze (aOR 1.17, 1.03-1.33) and presence of a concurrent neurological disorder (aOR 4.42, 1.70-11.48). Chest radiography was ordered more frequently among those readmitted (540/2,274 [23.7%] vs. 3,102/18,329 [16.9%], p < 0.001). Readmitted patients more frequently received second-line antibiotics (808/2,256 [35.8%] vs. 5,538/18,173 [30.5%], p < 0.001), TB medication (69/2,256 [3.1%] vs. 298/18,173 [1.6%], p < 0.001), salbutamol (530/2,256 [23.5%] vs. 3,707/18,173 [20.4%], p = 0.003), and prednisolone (157/2,256 [7.0%] vs. 764/18,173 [4.2%], p < 0.001). Inpatient mortality was 2,354/18,329 (12.8%) among children admitted with a first episode of severe pneumonia and 269/2,274 (11.8%) among those who were readmitted (adjusted hazard ratio (aHR) 0.93, 95% CI 0.82-1.07). Age (12-59 months vs. 2-11 months: aHR 0.62, 0.57-0.67), male sex (aHR 0.81, 0.75-0.88), malnutrition (WAZ <-3SD vs. WAZ >-2SD: aHR 1.87, 1.71-2.05); WAZ − 2 to -3 SD vs. WAZ >-2SD: aHR 1.46, 1.31-1.63), complete vaccination (aHR 0.74, 0.60-0.91), wheeze (aHR 0.87, 0.78-0.98) and anaemia (aHR 2.14, 1.89-2.43) were independently associated with mortality. Conclusions Children readmitted with severe pneumonia account for a substantial proportion of pneumonia hospitalisations and deaths. Further research is required to develop evidence-based approaches to screening, case management, and follow-up of children with severe pneumonia, prioritising those with underlying risk factors for readmission and mortality.